Prospek Masa Depan Dual Banking System Dalam Konteks Globalisasi Ekonomi Syariah - Samsudin, Agus Rojak; Mukhlas, Oyo Sunaryo; Rusyana, Ayi Yunus (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2024)
The primary challenge facing the global banking system is how conventional and Islamic banking systems can operate simultaneously and synergistically within the context of Islamic economic globalization. This study aims to analyze the future prospects of the Dual Banking System, which integrates conventional and Islamic banking, in supporting global economic stability and growth. The methodology employs a qualitative approach with descriptive analysis, incorporating literature review and secondary data analysis from research reports of international institutions focused on the Islamic finance industry. The findings indicate that the Dual Banking System has significant potential to enhance financial inclusion and offer ethical and stable investment alternatives. However, substantial challenges, such as non-uniform regulations and disparate business cultures, remain to be addressed. The implications of this research suggest that with more comprehensive regulatory support and improved financial literacy, the Dual Banking System can become a crucial pillar in fostering a more inclusive and sustainable global economy